Perancangan Konfigurasi Tinggi Setang, Sadel, dan Pedal Sepeda yang Ergonomis - Lusi Susanti; Yogi Hendra Agustion (Jurnal Optimasi Sistem Industri, 2015)
The bike is still one of the favorite modes of transportation as it is cheaper and environmentally friendly. However, some problems still arise in current bicycle design, one of which is a discrepancy between dimensions of the bike with anthropometry of the user. This has resulted in unneutral and uncomfortable posture for the users. This study focuses on providing optimum configuration of distance from saddle to pedal, the height of handle-bar, and distance from handlebar to saddle of the bike. Some physiological parameters such as the percentage of CVL (cardiovascular limit), energy consumption and Posture Evaluation index are measured to determine the optimum distance of handle-bar, distance from handlebar to saddle, and distance from saddle to pedal. Results show that it is necessary to modify the current dimension of the bike to accommodate three posture categories of Indonesia population: small posture (P5), medium (P50) and large posture (P95).